Coupled minimal models revisited II: Constraints from permutation symmetry - António Antunes, Connor Behan (SciPost Physics)
Coupling $N$ large $m$ minimal models and flowing to IR fixed points is a systematic way to build new classes of compact unitary 2d CFTs which are likely to be irrational, and potentially have a positive Virasoro twist gap above the vacuum. In this paper, we build on the construction of [A. Antunes and C. Behan, Phys. Rev. Lett. 130, 071602 (2023)], establishing that, for spins less than 10, additional currents transforming in non-trivial irreducible representations of the permutation symmetry $S_N$ are not conserved at the IR fixed points. Along the way, we develop a finer understanding of the spectrum of these theories, of the special properties of the $N=4$ case and of non-invertible symmetries that constrain them. We also discuss variations of the original setup of [A. Antunes and C. Behan, Phys. Rev. Lett. 130, 071602 (2023)], some of which can exist for smaller values of the UV central charge.